CD40 agonist-induced IL-12p40 potentiates hepatotoxicity - Wei Chen; Yan Qu; Shahram Salek-Ardakani; Graham Thomas; Jonathan Heyen; Javier Chaparro-Riggers; Caroline Bonnans; Wenqian He; Bernard Buetow; Min Liao; Breanna Jung; Smitha Pillai; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background CD40 is a compelling target for cancer immunotherapy, however, attempts to successfully target this pathway have consistently been hampered by dose-limiting toxicity issues in the clinic that prevents the administration of efficacious doses.Methods Here, using cytokine and cytokine receptor depletion strategies in conjunction with a potent CD40 agonist, we investigated mechanisms underlying the two primary sources of CD40 agonist-associated toxicity, hepatotoxicity and cytokine release syndrome (CRS).Results We demonstrate that CD40 agonist -induced hepatotoxicity and CRS are mechanistically independent. Historical data have supported a role for interleukin-6 (IL-6) in CRS-associated wasting, however, our findings instead show that an inflammatory cytokine network involving TNF, IL-12p40, and IFNγ underlie this process. Deficiency of TNF or IFNγ did not influence CD40-induced hepatitis however loss of IL-12p40 significantly decreased circulating concentrations of liver enzymes and reduced the frequency of activated CD14+MHCII+ myeloid cells in the liver, indicating a role for IL-12p40 in liver pathology.Conclusions As clinical research programs aim to circumnavigate toxicity concerns while maintaining antitumor efficacy it will be essential to understand which features of CD40 biology mediate antitumor function to develop both safe and efficacious agonists.